Combination Process of Rice Husk Ash Coagulation and Electrocoagulation for Palm Oil Mill Effluent Treatment - Lestari, Indriana; Amalia, Dwi; Prastistho, Widyawanto; Angin, Jeremia Bernadin Perangin; Zenatik, Muhammad Haekal (Eksergi, 2025)
Palm oil mill effluent (POME) poses a significant environmental threat due to its high organic and inorganic load. This study introduces a novel integration of rice husk ash (RHA) coagulation and electrocoagulation (EC) for sustainable POME remediation. Thermally treated at 500 °C for two hours, RHA was characterized via FTIR, revealing active silica-based functional groups conducive to charge neutralization and adsorption. Treatment experiments employed 9.3 g/L RHA and aluminum electrodes spaced 20 mm apart under varying currents of 10, 15, and 20 A over 15, 30, and 45 minutes. At the highest tested condition (9.3 g/L RHA, 20 A, 45 minutes), the integrated process achieved 78% total solids (TS) and 43% chemical oxygen demand (COD) removal, surpassing individual RHA coagulation removed 34% TS and 17% COD, while EC alone achieved 43% TS and 18% COD removal. The superior performance stems from synergistic flocculation, adsorption, and electroflotation. Compared to conventional methods, the combined RHA–EC system offers faster treatment, lower chemical and energy demands, and improved sustainability. These findings suggest a scalable solution for decentralized POME treatment, particularly in resource-limited palm oil-producing regions.